Student engagement and self-efficacy: effect on retention in the General Mathematics course at the National University, Costa Rica engagement and self-efficacy: effect on retention in the General Mathematics course at the National University - Aguilar Fernández, Eduardo (2026)
Student retention is a multifactorial and complex phenomenon that has been the subject of research at various educational levels. Therefore, the objective of this research was to evaluate the effect of academic commitment, teacher commitment, and self-efficacy on student retention in the General Mathematics course at the National University, Costa Rica. Data were collected from a sample of 617 students enrolled in the General Mathematics course during the first semester of 2023. A logistic regression model was estimated to verify the predictive power of teacher social commitment, academic commitment, and student self-efficacy on the influence of these variables on students' decision to remain in the course. The retention rate in General Mathematics was calculated to be 76.34%, and that the self-efficacy is a factor associated with student retention in General Mathematics (p < 0.0001), so that the probability of remaining in the course increased by 5% for each additional point a student gained in student self-efficacy (p < 0.0001). Statistically significant evidence suggests that self-efficacy is related to student retention in the General Mathematics course at the National University. Furthermore, no significant effect was observed on student retention in the course in either of the two dimensions of student commitment studied. However, further research is needed to explore the relationship between retention and the dimensions of student commitment, given the multifactorial nature of both constructs.